Sheep Commercialization in Bouake, Côte d’Ivoire: Price Variations at the Small Ruminants Market - G. Toure; Z. Ouattara; V. Yapy-Gnaore; T. Yo; K. G. Tanoh (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2005)
A survey based on a one-time questionnaire for sheep customers was conducted at the small ruminants market of Bouake. The aim was to determine the dynamics of sheep price during the year. In the data collected, which concerned animal price and some of their physical characteristics, a particular attention was given to the periods of major holidays. A total of 552 sheep commercialized at the market were included in the survey. The number of sheep sold a week before a holiday was higher than that of sheep sold after the holiday. The small ruminants market of Bouake was mainly supplied with imported sheep (81%) with a majority of the Sahelian type (60%). The traditional technique of defining sheep retail price with visual appraisal and without any measuring instrument provided similar results to those obtained when setting the price based on the exact weight. The traders proved to be quite experienced in that appraising activity. Live weights and holiday periods significantly affected the sheep price. Large sheep, mainly of Sahelian type, were specially sold over Muslim holidays. In the weeks preceding the holidays, the highest sheep price recorded was for the Tabaski (on average 39,705 CFAF per Sahelian sheep and 26,750 CFAF per Djallonke). The lowest sheep price was recorded for the Sahelian sheep at Christmas time (28,105 CFAF/head) and for the Djallonke sheep over New Year’s (17,937 CFAF/head). The sheep price was mainly related to animal weights and holiday periods throughout the year, which modulated the customer’s choice.